Error resilient image coding for radio channels - Chippendale, P.; Honary, B. (Gateway to 21st Century Communications Village. VTC 1999-Fall. IEEE VTS 50th Vehicular Technology Conference (Cat. No.99CH36324), 1999)
This paper explores the application of the error resilient coding scheme, absolute addressed picture element coding (APEL), to progressive image transmission over narrow-band radio channels, such as HF. Picture element (pel) interleaving strategies are explored and APEL coding and its merits are discussed. Demonstrated through air-trial results, this novel image coding approach are shown to restrict error propagation through its unique coding structure and offer reconstructed images of increasing definition as transmissions progress.